1966
DOI: 10.1507/endocrj1954.13.85
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Histochemistry in Experimental Diabetes Mellitus

Abstract: SYNOPSISReported here, are the observations on various histochemical enzyme reactions in several organs (the liver; the kidney; the cardiac, diaphragm, and femoral muscles; the duodenum; the adrenal gland) of rabbits which had been rendered diabetic for from 3 days up to 1 year or more. Independent of the diabetes-inducing reagents (Alloxan or Dithizone) used, the following similar results were obtained: With SD, LD and DPND (which are related to the Krebs cycle activity) and with such phosphatases as ACPase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

1968
1968
1972
1972

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
2
2
1
Order By: Relevance
“…They reported that SD activity in the kidney, especially in the cortex, increased gradually after alloxan injection. However, this finding is in clear disagreement with Ihara's observations of the kidneys of rabbits with alloxan diabetes (Ihara, 1966a). In the present experiment too, an obvious increase in activity was seen in the proximal and distal tubules of rats with either spontaneous or alloxan diabetes.…”
Section: Changes In Enzyme Activity In the Liver And Kidneycontrasting
confidence: 99%
See 4 more Smart Citations
“…They reported that SD activity in the kidney, especially in the cortex, increased gradually after alloxan injection. However, this finding is in clear disagreement with Ihara's observations of the kidneys of rabbits with alloxan diabetes (Ihara, 1966a). In the present experiment too, an obvious increase in activity was seen in the proximal and distal tubules of rats with either spontaneous or alloxan diabetes.…”
Section: Changes In Enzyme Activity In the Liver And Kidneycontrasting
confidence: 99%
“…This finding confirmed that of Ihara (1966a). Rudolph (1959) also demonstrated that ACPase and ALPase activities were clearly increased in the livers but decreased in the kidneys of rats with alloxan diabetes.…”
Section: Changes In Enzyme Activity In the Liver And Kidneysupporting
confidence: 77%
See 3 more Smart Citations